2009
DOI: 10.1021/jp903912q
|View full text |Cite
|
Sign up to set email alerts
|

Are the Ground States of the Later Actinocenes Multiconfigurational? All-Electron Spin−Orbit Coupled CASPT2 Calculations on An(η8-C8H8)2(An = Th, U, Pu, Cm)

Abstract: Spin-orbit free and spin-orbit coupled CASPT2 wave functions and energies are presented for the ground and low-lying excited states of four actinide element sandwich molecules; thorocene (ThCOT(2)), uranocene (UCOT(2)), plutonocene (PuCOT(2)), and curocene (CmCOT(2)). Spin-orbit coupling is found to make little difference to the equilibrium geometry of uranocene and plutonocene but has a significant effect on the energy spectrum of all the systems considered here other than thorocene. In all cases, however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 48 publications
5
57
0
Order By: Relevance
“…Historically, the first theoretical work on U(COT) 2 including relativistic effects was done by Pyykkö and Lohr in 1981 [100] using relativistically parametrised extended Hückel calculations. Whereas a single-determinant wave function could describe the ground states of thorocene and uranocene [194,195], a multiconfigurational description of the wave function is needed for the later actinides [196,197]. For example, Kerridge and Kaltsoyannis [196] performed all-electron spin-orbit coupling complete active space self-consistent field calculations including dynamic correlation via second order perturbation theory (SOC-CASPT2) for the ground and low-lying excited states of M(COT) 2 (M=Th, U, Pu, Cm).…”
Section: Assessing Covalency In Nitrogen Ligand-actinide Complexesmentioning
confidence: 99%
“…Historically, the first theoretical work on U(COT) 2 including relativistic effects was done by Pyykkö and Lohr in 1981 [100] using relativistically parametrised extended Hückel calculations. Whereas a single-determinant wave function could describe the ground states of thorocene and uranocene [194,195], a multiconfigurational description of the wave function is needed for the later actinides [196,197]. For example, Kerridge and Kaltsoyannis [196] performed all-electron spin-orbit coupling complete active space self-consistent field calculations including dynamic correlation via second order perturbation theory (SOC-CASPT2) for the ground and low-lying excited states of M(COT) 2 (M=Th, U, Pu, Cm).…”
Section: Assessing Covalency In Nitrogen Ligand-actinide Complexesmentioning
confidence: 99%
“…Computations of Pu‐containing molecules are still rather scarce in the literature, mainly because of the number of electrons contained in such systems and the treatment of relativistic/correlation effects. Previous studies33, 34, 35, 36 have shown that the metal−carbon bonds in the highly symmetric plutonocene molecule have a multiconfigurational character with significant contribution of static as well as dynamic electron correlations. In view of the low point symmetry and the considerable dimension of the Pu(1,3‐COT′′)(1,4‐COT′′) molecule, compromises in the selection of basis sets and the chosen methods had to be made.…”
mentioning
confidence: 94%
“…Subsequently, anionic complexes of the type K[An(COT) 2 ] (An=Np, Pu) were reported24, 25 and the series of neutral sandwich complexes was extended to a number of ring‐substituted derivatives such as An(EtCOT) 2 , An( n BuCOT) 2 , and An(Me 4 COT) 2 (An=Pa, Np, Pu) 25, 26, 27, 28. From the very beginning until today, the magnetic and electronic properties of these actinocenes and related sandwich complexes intrigued theoretical chemists 29, 30, 31, 32, 33, 34, 35, 36, 37, 38. For example, it was shown that, while 5f contributions to covalency in these actinocenes are smaller in magnitude than 6d contributions, the variation in covalency is almost entirely accounted for by the variation in the 5f contribution 36…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental and theoretical studies of certain Ce-and Yb-based organometallic complexes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] have highlighted the importance of multiconfigurational interactions in understanding their electronic, structural, and magnetic properties. The canonical examples include Ce(cot) 2 , also known as "cerocene," where cot = cyclooctatetraene = C 8 H 8 , and Cp * 2 Yb(bipy), where Cp * = pentamethylcyclopentadienyl, and bipy = 2,2 ′ -bipyridine.…”
Section: Introductionmentioning
confidence: 99%